Effects of livestock on guanaco Lama guanicoe density, movements and habitat selection in a forest-grassland mosaic in Tierra del Fuego, Chile - Moraga, Claudio A.; Funes, Martín C.; Pizarro Pinochet, Jose Cristobal; Briceño, Cristobal; Novaro, Andres Jose (Oryx)
Locally abundant ungulates often come into conflict with human activities. After a population collapse that reached its nadir in the 1970s, the guanaco Lama guanicoe population in Tierra del Fuego, Chile, recovered and is now in conflict with sheep ranching and commercial logging. We studied the effects of livestock density and environmental factors on guanaco abundance and spatial ecology, using seasonal counts and radio-telemetry in a private protected area (Karukinka) and neighbouring ranches in a forest–grassland mosaic in Tierra del Fuego. Guanaco density was highest in low-elevation areas with more grassland cover and little snow accumulation in winter. In low-elevation areas, guanaco density decreased with increasing livestock density. Radio-tracked guanacos exhibited a partial migration pattern: two individuals migrated seasonally, selecting grasslands and avoiding forests mainly in summer, whereas six sedentary individuals used habitats according to their availability. Migratory guanacos spent the summer in Karukinka and winter on nearby ranches. High sheep densities and poor range condition on the ranches reduce key forage resources available to guanacos and may promote use of forests by guanacos, affecting forest regeneration and increasing conflict with logging. Current guanaco harvest by loggers may fail to reduce the impact of guanacos on logged-forest regeneration if guanaco spatial ecology and sheep management are not considered. Our results provide insight into the interactions among guanacos, forests and livestock ranching, and may be used to reduce conflicts and guide conservation in the Fuegian ecosystem. Fil: Moraga, Claudio A. Wildlife Conservation Society. Chile Program; Chile Fil: Funes, Martín C. Wildlife Conservation Society. Patagonian and Andean Steppe Program; Argentina Fil: Pizarro Pinochet, Jose Cristobal. Wildlife Conservation Society. Chile Program; Chile Fil: Briceño, Cristobal. Wildlife Conservation Society. Chile Program; Chile Fil: Novaro, Andres Jose. Consejo ...